What is the value of a Health Verified Program. - Schumacher, Kash Tucker (Kansas State University, 2011)
The beef cattle industry is one of the last industries in production agriculture that is not heavily integrated. Therefore each segment of the industry is constantly looking for opportunities to increase the value of their cattle. In recent years, one of those opportunities available to cow-calf producers was verification of certain production practices (i.e. Age and Source, Natural, and Non-Hormone Treated). The value flows from the consumer to the cow-calf producer. The packers need these verified cattle to fill export contracts therefore they are willing to pay a premium for these types of cattle. The objective of the thesis was to determine the value of a Health Verified Program (HPV) to feedlot operators. HPV is not required to export beef like other verified programs, but it does verify the procedures that a group of calves has received from the previous owner. Since the feedlot is a deciding factor of value for HPV, feedlot managers were asked from across the United States not only what value they place on HPV but other questions that could be beneficial to others involved in the beef cattle industry. Regression models were used along with a correlation analysis to determine value. There is value to a health verified program along with other procedures that are available to cow-calf producers. Individual producers need to determine which verifications and procedures are economical and efficient for their individual operations with all factors considered.
Keywords: Health verification; Health value; Third-Party verification value; Value added program; Agriculture, General (0473); Economics (0501)